Myocardial ischemic post-conditioning protects the lung against myocardial ischemia/reperfusion-induced damage by activating GSK-3β - Gao,Wenwei (2017)
Abstract Purpose: To investigate whether modulating GSK-3β could attenuate myocardial ischemia reperfusion injury (MIRI) induced acute lung injury (ALI) and analyze the underlying mechanism. Methods: Male SD rats were subjected to MIRI with or without myocardial ischemic post-conditioning in the presence or absence of GSK-3β inhibitor. GSK-3β inhibitor was injected peritoneally 10min before MIRI. Lung W/D weight ratio, MPO, PMNs, histopathological changes, TUNEL, Bax, Bcl-2, IL-6, IL-8, IL-10, GSK-3β, and caspase-3 were evaluated in the lung tissues of all rats. Results: After MIRI, lung injury was significantly increased manifested as significant morphological changes and increased leukocytes in the interstitial capillaries, Lung W/D ratio, MPO, and PMN in BALF, which was associated with enhanced inflammation evidenced by increased expressions of IL-6, IL-8 and reduced expression of IL-10. MIRI significantly increased cell apoptosis in the lung as increased levels of apoptotosis, Bax, cleaved caspase-3, and reduced expression of Bcl-2 was observed, which was concomitant with reduced p-GSK-3β. All these changes were reversed/prevented by ischemic post-conditioning, while these beneficial effects of ischemic post-conditioning were abolished by GSK-3β inhibition. Conclusion: Myocardial ischemia reperfusion injury induces acute lung injury by induction of inflammation and cell apoptosis. Ischemic post-conditioning protects the lung from ALI following MIRI by increasing p-GSK-3β.